2011
DOI: 10.1038/onc.2011.211
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitosis and taxane response by Daxx and Rassf1

Abstract: Current theories suggest that mitotic checkpoint proteins are essential for proper cellular response to taxanes, a widely-used family of chemotherapeutic compounds. We recently demonstrated that absence or depletion of protein Daxx increases cellular taxol (paclitaxel) resistance—a common trait of patients diagnosed with several malignancies, including breast cancer. Further investigation of Daxx-mediated taxol response revealed that Daxx is important for the proper timing of mitosis progression and cyclin B s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 54 publications
1
41
0
1
Order By: Relevance
“…We have previously shown that Daxx protein participates in mitosis regulation, thus affecting taxane resistance. 20,21 According to our model, 21 Daxx-deficient cells cannot resolve prometaphase/ metaphase transition as efficiently as control cells. This would explain the observation that, upon taxane treatment, cells with a low Daxx expression are protected from mitotic catastrophe/slippage and are able to complete mitosis and survive after taxane decay.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…We have previously shown that Daxx protein participates in mitosis regulation, thus affecting taxane resistance. 20,21 According to our model, 21 Daxx-deficient cells cannot resolve prometaphase/ metaphase transition as efficiently as control cells. This would explain the observation that, upon taxane treatment, cells with a low Daxx expression are protected from mitotic catastrophe/slippage and are able to complete mitosis and survive after taxane decay.…”
Section: Resultsmentioning
confidence: 89%
“…We previously demonstrated that Daxx depletion causes stabilization of cyclin B1, thus blocking cells transiently in mitosis. 21 To test whether Daxx and USP7 cooperate to maintain this block, we monitored the stability of cyclin B in HEp2 cells depleted by control or USP7 shRNAs (Supplementary Figure S1a). Cells were synchronized in mitosis by either Taxol or Nocodazole exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting that both MST1 and Daxx have been observed to associate with mitotic checkpoint protein Rassf1. 44,45 In addition, Ferritin heavy chain (FTH1) may bind directly with Daxx to regulate apoptosis. 46 At this point, it remains unknown how Daxx mechanistically regulates the activity and cellular localization of MST1 and how MST1 and Daxx may interplay with Rassf1 and FTH1.…”
Section: Gck-ii Kinases Regulate Lymphocyte Adhesion Migration Prolmentioning
confidence: 99%